User satisfaction and its associated factors among members of a Norwegian clubhouse for persons with mental illness - Ritter, Victoria C.; Nordli, Hege; Fekete, Orsolya R.; Bonsaksen, Tore (International Journal of Psychosocial Rehabilitation, 2018)
For individuals experiencing mental illness, work may not be accessible such that alternatives to ordinary work are needed. Clubhouses provide work-oriented psychosocial rehabilitation for persons with mental illness, but little is known about the members' satisfaction with the clubhouse they use. This study ex- plored the members' level of satisfaction with the clubhouse experience, and examined factors associated with their satisfaction. A cross-sectional design was used. The data, originating from a member survey, were analyzed with linear regression. Based on eighty-nine valid responses, the study found that women were more satisfied with “personal outcome” compared with men. Members with less work experience were more satisfied with “user involvement” compared with those with more work experience, and the scores on all satisfaction scales increased with more frequent use of the clubhouse. Given the value of di- versity at the clubhouses, user satisfaction should be monitored and sustained for all members.